Implementation of Ukhuwah Islamiyah Education in Scout Activity Pondok Modern Darussalam Gontor Putri 2, Ngawi, Indonesia - Agus Budiman; Nidya Fairuz Zanaya (Educan : Jurnal Pendidikan Islam, 2018)
The purpose of this research is: (1) to know education ukhuwah islamiyah applied on children scouting activities in a Modern Islamic boarding school Darussalam Gontor  two for girls Mantingan Ngawi Java Indonesia the years 2017-2018. (2) to know the application of educational Activities in Scouting Ukhuwah Islamiyah in Modern Islamic boarding school Darussalam Gontor two for girls Mantingan Ngawi Java Indonesia the years 2017-2018. d. research is the research field (field Research). As for the type of field research is Qualitative Research. To get the necessary data, the researchers used a method of observation, interview and documentation, so getting a clear description about the implementation of educational activities in Scouting ukhuwah islamiyah. school year to analyze the data, researchers using data analysis Miles and Huberman that includes three research measures namely: data collection, display or study of the data and the conclusion or verification. The results of the research done indicates that: (1) education ukhuwah islamiyah in scouting activities in a Modern Cottage Darussalam Gontor two for girls, the activity of bodyguard or escort continued support to members to obtain values education ukhuwah islamiyah in activities Scouting. (2) implementation of educational activities in Scouting ukhuwah islamiyah in Modern Cottages Darussalam Gontor two for girls is implemented through: a) inculcation of values education ukhuwah islamiyah activities in Scouting by the Builder to the Member directly. b implementation of the ukhuwah islamiyah education) by using method example (qudwah hasanah). c) implementation education ukhuwah islamiyah through scouting activities in a member of liveliness.